Polly Diamond and the magic book - Kuipers, Alice, 1979- (Kuipers, Alice, 1979- Polly Diamond, 2018)
Polly loves words, writing, and telling stories, so when she finds a fancy book on her doorstep labeled "Special Delivery from the Writing and Spelling Department for Polly Diamond" she is thrilled; and when she finds that anything she writes in it actually happens she is really excited--but Polly soon realizes that she has to be very careful what she writes because that kind of power can be dangerous.